Population Dynamics of Insect Pests of Pea - Tare, Shraddha; Khandwe, Nanda; Naveen (Indian Journal of Entomology, 2023)
The seasonal incidence of major insect pests on pea Pisum sativum at different growth stages has been assessed in this study. Major pests observed include gram pod borer Helicoverpa armigera (Hubner), blue butterfly Lampedes boeticus (L.), pea leaf miner Chromatomyia horticola Goureau and pea aphid Acyrthosiphon pisum (Harris). These results revealed that peak incidence of H. armigera (7.80 larvae/ plant) and L. boeticus (8.60 larvae/ plant) was during the 8th and 9th SMW, respectively; while for C. horticola (5.50 larvae/ leaf) and A. pisum (94.1 aphids/ plant) it was 5th SMW. Helicoverpa armigera incidence revealed a significant negative correlation with minimum temperature (r= -0.628) while for L. boeticus it was positive one with maximum temperature (r= 0.604). The incidence of C. horticola was observed to be significantly negatively correlated with minimum temperature and rainfall (r= -0.826 and r= -0.584, respectively); while A. pisum revealed a significant negative correlation with minimum temperature (r= -0.806).